ACCURATE ONLINE E-MODULE IN COMPUTER ACCOUNTING COURSE - Firnanda, Yolla; Sulastri, Sulastri (Universitas PGRI Madiun, 2024)
ABSTRACT This study aims to develop valid, effective, accurate online e-module teaching materials as an alternative solution to the problem of limited resources for accurate online computer-based subject learning in the accounting field. This research and development utilized the 5-stage ADDIE model. The data collection techniques used were interview guides, expert validation forms, and restricted users and testing. The participants of this study include several accounting teachers and students, one media expert, two material experts, eight limited-user students, 35 students in the experimental class, and 33 students in the control class. The results show that the precise online electronic module received 98% from media experts, 95% from material experts, and 95% from limited users. Therefore, the E module is suitable for use in teaching. The significance of the T-test result indicating that the E module effectively improves accounting computer learning effects. ABSTRAK Studi ini dimaksudkan untuk mengembangkan bahan ajar e-modul Accurate Online sebagai alternatif solusi atas permasalahan keterbatasan sumber belajar pada mata pelajaran komputer akuntansi berbasis Accurate Online yang tervalidasi dan efektif. Penelitian dan pengembangan ini menggunakan model pengembangan ADDIE dengan 5 tahapan penelitian. Teknik pengumpulan data yang digunakan yakni pedoman wawancara, lembar validasi ahli dan pengguna terbatas, serta tes. Subjek penelitian ini terdiri atas beberapa guru dan siswa jurusan Akuntansi, seorang ahli media, dua orang ahli materi, delapan siswa sebagai pengguna terbatas, 35 siswa bertindak sebagai kelas eksperimen dan 33 siswa sebagai kelas kontrol. Hasil penelitian diperoleh bahwa e-modul Accurate Online mendapat nilai 98% dari ahli media, 95% dari ahli materi, dan 95% dari pengguna terbatas. Sehingga e-modul dikatakan layak untuk digunakan dalam pembelajaran. Sementara hasil uji T menunjukkan bahwa e-modul efektif untuk meningkatkan hasil belajar komputer akuntansi.